La "Aggadat Mašiaḥ": traduzione e commento di un testo escatologico medievale ebraico - Crestani, Sebastiano (Liber annuus, 2020)
For the first time in italian, this work offers a translation of the Aggadat Mašiaḥ, a medieval eschatological midrash which is part of the Midraš Leqaḥ Ṭov by Rabbi Ṭuviyyah ben Eliʿezer (end of 11th - beginning of 12th century) to comment on a messianically relevant biblical verse such as Num 24:17. The analysis and commentary of the text reveal a wealth of themes and aim to not only highlight its origins and importance in the history of Jewish thought, but also its recurrence in other medieval eschatological works, be it Jewish, Christian or Muslim. Special attention is also paid to the figure of Messiah ben Yosef, the true protoganist of the midrash, and his function as a suffering messiah, warrior and priest.